Methodology and Research Design of Islamic Education Management - Sutijah; Nurul Hidayati Murtafiah (MultiTech Publisher, 2023)
This study is defined that the Islamic education method is where the general steps for conveying material so as to be able a number of presumptions concerning the characteristics of Islam as a supersystem are used to achieve educational objectives. Islamic teaching methods are practical procedures that a teacher takes when conducting class instruction. As a result, the method is a statement of the fundamental presumptions of the Islamic material approach, and the technique is how the method is put into practice.This study used a sort of qualitative research known as a literature study approach, which reads, records, and analyzes a variety of sources, including books, journals, and other literature, as a source of research data.According to the study's findings, Islamic education is the process of assisting someone in growing spiritually and physically in accordance with Islamic principles Muslim character. The process of building or managing Islamic educational institutions that engages Muslim human resources and motivates them to successfully and efficiently accomplish the objectives of Islamic education is what is meant by